68.5k views
20 votes
PLEASE HELP I'M BEGGING YOU SHOW STEPS IF YOU CAN

1.)Write -2x^3 (4x^3+5x^6) In Standard form, classify the degree and find the end behavior


2.) What Are The Zeros of the function and what are their multiplicities

f(x) =x^3+15x^2 +63x+49

1 Answer

5 votes

Answer:

Question 1

Given expression:


-2x^3 (4x^3+5x^6)

Apply the distributive law
a(b+c)=ab+ac:


\implies -2x^3 \cdot4x^3+-2x^3 \cdot 5x^6

Multiply the numbers:


\implies -8x^3 x^3-10x^3 x^6

Apply exponent rule
a^b \cdot a^c=a^(b+c)


\implies -8x^6-10x^9

In standard form we write it in order from the greatest degree:


\implies -10x^9-8x^6

Therefore, as the polynomial is degree 9, it is a nonic polynomial.

End behaviors

As the leading coefficient is negative and the leading degree is odd:


f(x) \rightarrow + \infty \textsf{, as } x \rightarrow - \infty


f(x) \rightarrow - \infty \textsf{, as } x \rightarrow + \infty

----------------------------------------------------------------------------------------------

Question 2

Factor the given function to find the zeros

Given function:


f(x) =x^3+15x^2 +63x+49


f(-1) =(-1)^3+15(-1)^2 +63(-1)+49=0

Therefore
(x+1) is a factor of the function


\implies x^3+15x^2 +63x+49=(x+1)(x^2+bx+49)


=x^3+(b+1)x^2+(b+49)x+49

Comparing coefficients ⇒ b = 14


\implies x^3+15x^2 +63x+49=(x+1)(x^2+14x+49)

Factoring
(x^2+14x+49):


\implies (x^2+14x+49)=(x+7)(x+7)=(x+7)^2

Therefore,


f(x)=(x+1)(x+7)^2

To find the zeros, equate to the function zero:


(x+1)(x+7)^2=0

Therefore,


x+1=0 \implies x=-1 \textsf{ with multiplicity 1}


x+7=0 \implies x=-7\textsf{ with multiplicity 2}

User Brave Sir Robin
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.